Modernisasi dan Perubahan Sosial Masyarakat Desa Lala Kabupaten Buru - Rusdi, M.; Sangaji, Radi Udin Alfian; Rumkel, Lutfi; Emba, Munawwarah; Ismail, Ismail (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to describe the effect of modernization on social change as well as the inhibiting and supporting factors. The next goal is to reveal and explain the positive values contained in modernization and social change. This research is a descriptive qualitative research. Informants are determined by purposive sampling. Data collection is done by; observation, interview, and documentation. As well as data analysis is carried out in stages; data reduction, data presentation and data verification. The results of the study explain that the effect of modernization on social change is; scientific thinking and lifestyle changes. At first the people in meeting their daily needs, they took advantage of the natural surroundings. However, with the entry of modernization they began to follow the lifestyle that characterizes modern society. Several factors supporting the occurrence of modernization and social change, namely; heterogeneous society, dissatisfaction in various fields of life, and the perspective of humans who must improve their standard of living. While the inhibiting factors are; attitudes that are still traditional, the emergence of fear of shakiness of integration, and bad prejudice against elements of foreign culture.